O direito à paisagem urbana: imagem e afetividade na construção de uma geografia do olhar - Silva, Silvia Heleny Gomes da (2019)
The city is not just its physical structure. It is built, sustained, confirmed and resignified from the mutual relationship between itself and the people who move it and make it vivid through symbolic exchanges woven with spaces and places. These exchanges between the city environment and people are primarily due to the way individuals move about it and how they perceive it. In this sense, the present study aimed to understand how inhabitants of the city of Fortaleza build images and affectivities with the urban landscape from their geography of the eye, considering the question: What is the importance of landscape in people's lives and what role does it play? It is crucial to consider that the landscape speaks from a place that is permeated with stories, feelings and emotions. People talk about places, just as places talk about them. This relationship is dialogical and reciprocal. What affects are involved in people's right to the landscape, both when contemplated and/or limited? This is the research problem of the present work. Therefore, the realization of this work was based on theoretical concepts in the areas of Psychology, Geography, Architecture, Anthropology, Sociology, Urban Law, and perspectives of Image and Photography. The field research counted on the insertion of the researcher in several neighborhoods of Fortaleza, totaling the seven administrative regions of the city territory. As a methodological tool we used the Affective Map Generating Instrument (IGMA) together with the Environmental Narrative and Photography, thus being characterized within the qualitative method. The results showed that the urban landscape goes beyond its materiality and enters into very subjective questions. Evoking affectivities of fear, insecurity, abandonment, joy, longing, love, well-being and uncertainties. To know the city of Fortaleza from the affection of its inhabitants, taking the landscape as a reference, is to have direct contact with the urbanity that often goes unnoticed in everyday life. To read landscapes is to read the space in which it is contextualized, as well as to learn about man's ways of socially organizing himself in the creation of territories and places.